On Saigo Fractional $q$-Calculus of a General Class of $q$-Polynomials - Biniyam Shimelis; Dayalal Suthar (Sahand Communications in Mathematical Analysis)
In this paper, we derive Saigo fractional $q$-integrals of the general class of $q$-polynomials and demonstrate their application by investigating $q$-Konhouser biorthogonal polynomial,  $q$-Jacobi polynomials and basic analogue of the Kamp$\acute{e}$ de F$\acute{e}$riet function. We have also derived polynomials as a specific example of our significant findings.